Analisis Struktur Kepemilikan, Faktor Eksternal, Internal Terhadap Struktur Modal, Dividen, Nilai Perusahaan Manufaktur - Nurianah, Nurianah; Anshori, Muslich (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
This study discusses and analyzes the Ownership Structure, External Factors, Internal Against Capital Structure, Dividends and Company Value. The population used in this study is companies listed on the Indonesia Stock Exchange using 37 companies. The data used are from 2010 to 2019, this study uses descriptive statistical analysis and inference with Structural Equation Modeling (SEM). The analysis shows: ownership structure does not oppose capital structure, dividend policy, and firm value, external factors affect internal factors, external factors do not oppose capital structure, external factors do not significantly influence firm value, internal factors related to capital structure, factors internal does not oppose dividend policy, internal factors oppose company value, capital structure opposes dividend policy, dividend policy has no effect on capital structure, capital structure is related to company value, and dividend policy is related to company value. Keywords: Ownership Structure; External and Internal Factors; Dividend Policy; Manufacture.